Hysteretic Friction of a Sliding Rubber Element - Lindner, Markus; Sextro, Walter; Popp, Karl (PAMM)
Friction, especially friction of elastomers, can cause acoustic problems like noise, squeal and comfort drawbacks like vibrations and wear. Therefore, rubber friction affects the function of many products in technical applications, e.g. seals, belts and tires. It can be classified according to different physical phenomena like adhesion, hysteresis, cohesion and viscous friction, see [3]. The topic of this paper is hysteresis friction of rubber that is caused by the energy dissipation due to internal material damping during the process of deformation. The deformation itself occurs during the sliding of a rubber element across the micro-scaled asperities of a rough surface. In this paper, the sliding process of a rubber element over real surfaces is simulated in time domain and compared to experiments. (Â{©} 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Stress mode dependent weighting functions for simulation of asymmetric creep effects - Mahnken, Rolf (PAMM)

Erzwungene Schwingungen von elastischen Mehrkörpersystemen mit Reibkontakten - Genzo, Alexander; Sextro, Walter; Popp, Karl (PAMM)
Im Folgenden wird eine Berechnungsmethode vorgestellt, die es erlaubt, das räumliche Schwingungsverhalten eines elastischen Mehrkörpersystems (EMKS) mit Reibkontakten in rechenzeit- und speicherplatzsparender Form zu analysieren. Der von trockener Reibung und Mikroschlupf geprägte, nichtlineare Dämpfungsmechanismus in den Reibkontakten eines EMKS wird dabei realitätsnahe abgebildet. Die Plausibilität der mit der Methode gewonnenen Berechnungsergebnisse wird beispielhaft an einem einfachen EMKS, einem in Längsrichtung geteilten, einseitig eingespannten Balken gezeigt. Für den geteilten Balken werden die Frequenzgänge des Torsionswinkels um die Längsachse und der Auslenkung um die biegeweiche Achse berechnet.

Design of Friction Dampers for Mistuned Bladed Disks - Panning, Lars; Sextro, Walter; Popp, Karl (PAMM)
Friction damping devices such as underplatform dampers are widely used in turbomachinery applications to reduce blade vibration amplitudes. In this paper, a model is presented briefly to calculate the forced response of mistuned bladed systems with friction dampers. Some results will give an insight in the vibrational behavior of frictionally damped bladed disks and how the damping gain is affected by the damper properties.

Anisotropic creep modeling based on elastic projection operators - Mahnken, Rolf (PAMM)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)